Examining the role of linguistic characteristics of task performance in integrated multimodal viewing-to-write tasks - Kormos, Judit; Brunfaut, Tineke; Bánfalvi, Borbála (Studies in Second Language Learning and Teaching, 2026)
This study investigates how second language (L2) writers’ textual features vary across multimodal integrated tasks and how these features relate to raters’ evaluations of performance. Reflecting the growing emphasis on multimodality in language use, our research focused on viewing-to-write tasks that combine auditory, visual, and written input. A total of 133 intermediate to advanced L2 English learners completed two task types: (1) viewing-to-describe, where participants watched a recording explaining and visually depicting a production process before writing a description; and (2) viewing-to-compare-and-contrast, where learners viewed a videocast of two experts discussing a topic, supported by visuals, and then produced a comparative report. Performances were evaluated using a purpose-developed rating scale, and the written texts were analyzed for linguistic features, including accuracy, cohesion, lexical diversity and sophistication, and syntactic and lexical complexity. Results showed that these linguistic indices explained a substantial proportion of variance in performance scores. Although the overall use of linguistic features did not differ significantly between task types, their relative contribution to scores varied. The findings have important implications for using multimodal integrated tasks in task-based language teaching and assessment.